Perbandingan Pengaruh Latihan Zig-zag Cross-over Shuffle dengan Latihan Bag weaves Terhadap Peningkatan Kelincahan - Husna, Nurul; Risma, Risma; Rustiawan, Hendra (Jurnal Keolahragaan, 2024)
The study was conducted to examine agility as a dependent variable. The method uses pre-experimentation. Pretest-posttest two group design is the design used. The research location is SMP Negeri 2 Sukaraja, Tasikmalaya Regency. The number of subjects was 30 people. Subject selection applied total sampling method. Data analysis applies SPSS 24. The measuring tool is the zig zag run test. The results of the study are: 1. The zig-zag cross-over shuffle exercise has an effective role in positive changes in the agility of students at SMP Negeri 2 Sukaraja, Tasikmalaya Regency. Bag weaves training has an effective role in positive changes in the agility of students at SMP Negeri 2 Sukaraja, Tasikmalaya Regency. 3. It can be seen that there is a difference between the zig-zag cross-over shuffle exercise and bag weaves which are effective for positive changes in the agility of students at SMP Negeri 2 Sukaraja, Tasikmalaya Regency. Conclusion: Data shows that group A (zig-zag cross-over shuffle) and group B (bag weaves) play an effective role in positive changes in student agility at SMP Negeri 2 Sukaraja, Tasikmalaya Regency.Studi yang dilakukan untuk meneliti kelincahan sebagai variabel terikat. Metode menggunakan pre-eksperimen. Pretest-postest two group design merupakan desain yg dipakai. Lokasi penelitian di SMP Negeri 2 Sukaraja Kabupaten Tasikmalaya. Jumlah subjek yaitu 30 orang. Pemilihan subjek menerapkan cara total sampling. Analisis  data menerapkan SPSS 24. Alat ukurnya adalah zig zag run test. Hasil studi yaitu: 1. Latihan zig-zag cross-over shuffle  memiliki peran yang efektif untuk perubahan positif kelincahan siswa SMP Negeri 2 Sukaraja Kabupaten Tasikmalaya. Latihan bag weaves memiliki peran yang efektif untuk perubahan positif kelincahan siswa SMP Negeri 2 Sukaraja Kabupaten Tasikmalaya. 3. Terlihat adanya ketidaksamaan antara latihan zig-zag cross-over shuffle  dengan bag weaves yang efektif untuk perubahan positif kelincahan siswa SMP Negeri 2 Sukaraja Kabupaten Tasikmalaya. Kesimpulan: Kelompok A (zig-zag cross-over shuffle ) dan kelompok B (bag weaves) secara data adanya peran yang efektif untuk perubahan positif kelincahan siswa SMP Negeri 2 Sukaraja Kabupaten Tasikmalaya.